Histamine Receptors and Their Ligands - Kitbunnadaj, Ruengwit (Asian Health, Science and Technology Reports, 2005)
Histamine, a biogenic amine, mediates multiple physiological effects through binding to its receptors, i.e., H1, H2, H3, and H4 receptors. Currently, the histamine receptors have taken attention as important targets for the treatment of several diseases and disorders. In this article, a short review about histamine, histamine receptors, and histamine receptor ligands is described in the state of art in molecular biology, pharmacology, and medicinal chemistry.